Seven year follow up of children presenting to the accident and emergency department with irritable hip. Issue 5 (1st September 1999) - Mattick, A; Turner, A; Ferguson, J; Beattie, T; Sharp, J
Abstract : OBJECTIVE: To assess an established protocol for managing children with irritable hip in the accident and emergency department. METHODS: Retrospective seven year follow up of all children managed under an established hip pain protocol. The main outcome measure was of failure of the protocol to identify serious pathology. RESULTS: A total of 103 children met the criteria for assessment using the protocol. Sixty were allowed home, and outpatient follow up arranged. All of these children except one were diagnosed as having transient synovitis. This child had Perthes' disease and was diagnosed at first presentation. Forty three children were admitted, with eight subsequently having a diagnosis other than transient synovitis of the hip. It was possible to review 80 children seven years later. Of these children no long term problems were encountered. CONCLUSION: The protocol used in the department for children with irritable hip is successful in identifying those children with transient synovitis of the hip, or other benign causes, and therefore not requiring hospital admission. Long term follow up showed that no serious pathology was missed.